Daya Hambat Fraksi n-heksan, Etil Asetat, dan Air dari Ekstrak Etanol Bunga Cengkeh (Syzygium aromaticum (L.) Merrill & Perry) Terhadap Bakteri Staphylococcus epidermidis - Ratih Armay Gustari; Nofran Putra Pratama; Kurnia Rahayu Purnomo Sari (JOURNAL OF PHARMACEUTICAL (JOP), 2023)
Background: Clove flower plants are known as traditional plants that can be used in food, drink and medicine. Clove flower ethanol extract (Syzygium aromaticum (L.) Merrill & Perry) has antibacterial activity. Antibacterial is a substance that can interfere with the growth or kill bacteria by interfering with the metabolism of harmful microbes.Objective: This study was conducted to determine how effective the n-hexane, ethyl acetate, and water fractions from clove the ethanol extract of clove flower (Syzygium aromaticum (L.) Merrill &Perry) in inhibiting the growth of Staphylococcus epidermidis bacteria.Method: Extract were made by the maceration method with 70% ethanol as a solvent. Then proceed with the fractionation process using a liquid-liquid extraction method using three solvents, namely n-hexane solvent (non-polar), ethyl acetate solvent (semi-polar), and water solvent (polar). Identification of clove flower extract and fraction flower was carried out by organoleptic test, phytochemical screening test, and thin layer chromatography test. A Bacterial inhibition test was carried out using the Kirby-Bauer disc diffusion method using concentrations of 20%, 40%, 60%, 80% and 100% with positive control used chloramphenicol while the negative control used distilled water.Result: The results of the n-hexane and ethyl acetate fraction had bacterial inhibition at concentrations of 60%, 80%, and 100%. The water fraction had a zone of bacterial inhibition at 100% concentration.Conclusion: Based on the results of the study was found that the n-hexane, ethyl acetate, and water fractions had effectiveness in inhibiting the growth of Staphylococcus epidermidis bacteria.